Clinical Significance of Lymphoscintigraphy Findings in the Evaluation of Lower Extremity Lymphedema - Karaçavuş, Seyhan (Mol Imaging Radionucl Ther, 2015)
OBJECTIVE: The purpose of this study was to investigate the clinical significance of lymphoscintigraphy imaging in the evaluation of lower extremity lymphedema. METHODS: Technetium-99m-labeled nanocolloid was injected subcutaneously in the first web spaces of both feet of 123 patients (M/F: 43/80, mean age 57.5±13.1 years, range 16-78 years) who had clinical evidence of lower extremity swelling with suspicion of lymphedema, and were referred for routine lymphoscintigraphy. Lymphoscintigraphy scan was started as dynamic viewing followed by static whole body imaging at 10 minute, 1 hour and 4 hours after injection. RESULTS: Eighty-seven patients had lymphedema. Patients who had lymphedema were divided into two groups according to their scintigraphy findings: Group I included 58 patients without uptake in the popliteal nodes, and group II included 29 patients with positive popliteal nodes. The rate of popliteal node visualization was higher in patients with dermal backflow as compared to those without dermal backflow (p<0.001). The duration of lymphedema was also longer in patients with dermal backflow and popliteal nodes (p<0.004). CONCLUSION: Lymphoscintigraphy is a reliable, easily applied and well-tolerated objective method to diagnose lower extremity lymphedema. Uptake by popliteal lymph nodes and the presence of dermal backflow on lymphoscintigraphy, which is performed for evaluation of the lower limb lymphedema, were important signs indicating longer disease duration and higher severity of lymphatic dysfunction.